Comparing facility management strategies in public secondary schools in Gauteng: a comparative case study of former Model C schools and previously disadvantaged schools in South Africa - Nkuta, Lungile D. (My University, 2015)
South Africa is a country that has been plagued by many social ills of the past due to its history that segregated the nation in terms of race. The impacts of this have been seen in many sectors within the country and one of such areas is education. School systems in many countries especially those in extreme poverty areas experience a substantial amount of building decay as compared to schools with excellent building conditions normally found in suburban areas. There is value in maintaining these structures. “The racially discriminatory system of education spending under the apartheid system, has bequeathed to this country and the Gauteng province in particular a public school system in which some schools are much better resourced than most other schools in the system.” (Judge Mbha, 2011, per comm.) The review of literature showed that there are variances within the public school system in South Africa especially those relating to the building conditions and the impact that they could ultimately have on the learner’s outcomes. Hence in order to offer solutions to one of South Africa’s most important commodity “education”, this research aims to examine the current policies and compare facilities management maintenance methods utilized in former “Model C” and former Department of Education (disadvantaged) public schools, and to identify and recommend the methods utilized in schools with a higher standard of maintenance and physical facilities management (FM) policies. Using the case study method of qualitative research, data were collected through semi-structured questionnaires complemented with interviews. The principals and custodians of school facilities conveyed various levels of understanding of school facilities management policies and implemented them similarly in certain aspects and differently in areas of management. These are visible in the physical fabric condition of the school. Former Model C schools facilities are still managed more efficiently. The recommendations are that the DBE finalizes the maintenance document that will guide schools on how to manage their facilities efficiently. Benchmarking and bestpractice of FM methods should be used in schools, and lastly equipping the general workers of schools with various building trades allows school facilities to be managed more effectively. Keywords: Facilities Management, Facilities Management Strategies, Former Model C, Previously Disadvantaged, South African Ordinary Public Schools.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Building.
Keywords: South Africa; School facilities; Planning; Schools; Sociological aspects